Effects of different standard and special diets on cognition and brain mitochondrial function in mice. (2nd September 2022) - Reutzel, Martina; Grewal, Rekha; Esselun, Carsten; Petry, Sebastian Friedrich; Linn, Thomas; Brandt, Annette; Bergheim, Ina; Eckert, Gunter P.
ABSTRACT: Objectives: Human nutrition plays an important role in prevention or at least slowing down the progression of age- and diet-related diseases. Thereby, mitochondrial dysfunction represents one common underlying mechanism, which is being investigated in mouse models. However, the influence of the selected diets in preclinical studies on cognition and mitochondrial function has not yet been reported cohesively. Methods: Therefore, we present the results of three different studies that addressed this question. First, we investigated the influence of two standard control chow diets and a special diet low in antioxidants over 6 months in aged NMRI mice. Additionally, a 70% high-fat (HF) chow diet as well as a western-style diet (WSD) rich in lard and fructose were examined in C57/BL6 mice. Cognitive performance, mitochondrial function and bioenergetics in the brain were investigated. Moreover, cerebral expression of genes involved in biogenesis and antioxidant defence (citrate synthase, complex I, complex IV, SOD2, Cat1, GPx-1) were quantified. Results: The results show that a modified, low antioxidant diet increased ATP levels in the brain of aged mice, while cognitive functions remained largely unaffected. A HF diet also showed significant effects on ATP levels and gene expression levels of relevant antioxidant markers, while the WSD had marginal effects on mitochondrial function and bioenergetics in the brain. Discussion: Our results indicate that standard- and special diets have an impact on cognition and mitochondrial function in the brain. Thus, appropriate caution is warranted when selecting a suitable diet for preclinical studies in mice.